(untitled) (Physical Education, Health and Social Sciences, 2026)
Conservation Agriculture (CA) is a sustainable farming system built on three core principles minimum soil disturbance, permanent organic soil cover, and species diversification that aims to reverse soil degradation, enhance ecosystem services, and ensure long-term crop productivity. This review synthesizes evidence demonstrating that CA significantly improves soil physical, chemical, and biological health compared to conventional tillage systems. Key benefits include enhanced aggregate stability and water infiltration rates, increased soil organic carbon (SOC) sequestration (0.1–0.93 Mg/ha/year depending on environment), improved nutrient cycling (notably higher available P and K), elevated microbial biomass and fungal diversity, and substantial increases in earthworm populations that contribute to nitrogen mineralization and yield gains. These changes translate into greater resilience against abiotic stresses such as drought and heat waves, with long-term trials showing yield increases of up to 9.3% under warming conditions and superior water-use efficiency in rainfed environments. However, short-term yield penalties, herbicide resistance risks, residue competition in mixed crop-livestock systems, high mechanization costs, and challenges in managing soil acidity in no-till systems remain important barriers, particularly for smallholder farmers in developing regions. Integrated weed management, precision technologies, adaptive liming strategies, and service-provision models for machinery are identified as critical pathways to overcome these constraints. Overall, when correctly implemented and locally adapted, CA offers a proven strategy for restoring soil health, stabilizing yields, mitigating climate change impacts, and advancing sustainable intensification of global agriculture.